Information acquisition and assimilation capacities as determinants of technological niche markets - Francisco Javier Santos Arteaga; Madjid Tavana; Debora Di Caprio (Journal of Innovation & Knowledge (JIK), 2022)
We present an equilibrium model where the demand side of the market determines the strategic incentives of firms when considering the introduction of technologically superior products (TSPs) and the subsequent dynamic evolution of the market configuration. Market demand is built on conventional features defining the behavior of decision-makers (DMs), who are required to acquire information sequentially about the characteristics describing the products. Firms may signal the introduction of TSPs, though only sufficiently experimental DMs update their beliefs when selecting a product from a firm. That is, technological habits and inertia condition the incentives of DMs to acquire information and select potential products within a market. In particular, the choices made by the DMs will be determined by their capacity to assimilate signals describing the introduction of TSPs and their attitude towards risk. We identify the conditions required for the emergence of technological niche markets allowing firms that signal the introduction of TSPs to thrive.
Keywords: L15; L13; O33; 650; information acquisition; Information assimilation; Niche markets; Signaling; Technological evolution; Technology demand